Speckle pattern formation in spatially limited optical systems - M.M. Kotov (Semiconductor Physics, Quantum Electronics & Optoelectronics, 2016)
The dependences of statistical parameters inherent to speckle patterns on the object roughness and aperture size have been investigated. The experimental results that confirm theoretical dependence quality within the limits of errors were obtained. It has been shown that spatial finiteness of the optical system causes significant changes of transferred field.